2005
DOI: 10.1111/j.1365-2214.2004.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐year follow‐up of orphans’ competence, socioemotional problems and post‐traumatic stress symptoms in traditional foster care and orphanages in Iraqi Kurdistan

Abstract: Even if the two orphan care systems showed more similarities than differences, the foster care revealed better outcomes over time. The results are discussed in relation to gender, age, socio-economic situation, cultural values and the characteristics of each care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 34 publications
0
34
2
4
Order By: Relevance
“…The evidence base across multiple studies emphasizing cultural and other contextual features guiding the development of specific intervention approaches or adaptations of interventions ranges from poor to strong (Ahmad et al, 2005;Annan et al, 2008;International Labour Organization, 2007;Peters, 2007;Wessells, 2009). An understanding of the cultural context is needed when one is developing or sustaining interventions that address the needs of vulnerable populations of children and youth.…”
Section: Child Protection Systems and Children Outside Of Family Carementioning
confidence: 98%
“…The evidence base across multiple studies emphasizing cultural and other contextual features guiding the development of specific intervention approaches or adaptations of interventions ranges from poor to strong (Ahmad et al, 2005;Annan et al, 2008;International Labour Organization, 2007;Peters, 2007;Wessells, 2009). An understanding of the cultural context is needed when one is developing or sustaining interventions that address the needs of vulnerable populations of children and youth.…”
Section: Child Protection Systems and Children Outside Of Family Carementioning
confidence: 98%
“…Unfortunately, however, residential institutions such as orphanages are unlikely to provide resources for children specifically to help them to cope with their exposure to traumatic events. Furthermore, these facilities may in fact exacerbate traumatic stress symptoms, given the inadequate psychological support that exists in many of these settings [15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…In the research on orphans, the role of psychosocial status on multiple outcomes has been studied, though not specifically in relation to learning outcomes. Research on OAC in low and middle income countries found that orphaned children are more susceptible than non-orphans to exposure to potentially traumatic events due to lack of adequate adult protection [18][19][20][21]. A recent study found that OAC anxiety and emotional difficulties increased with additional exposure to potentially traumatic events [22].…”
Section: Introductionmentioning
confidence: 99%